Conflict and Its Resolution in Indonesian Islam: A Case Study of a Javanese Muslim Society in Riau - Imron Rosidi; Maulana Maulana; Khotimah Khotimah (Sunan Kalijaga: International Journal of Islamic Civilization, 2018)
This paper aims to examine the extent to which a Muslim society in Indonesia solves its conflict. By using a Muslim society in Riau as a case study, this article argues that the society observed has a unique characteristic which may differ from other Muslim societies in other regions. It proposes that, in this community, the negotiation is done silently to shape the peaceful social interaction and harmonious relationship. In fact, the conflict within this society is actually corrosive when the elites have basically different education background categorized into Pesantren and University graduates making diverse ideas about religious and educational issues. The conflict is identified to be hybrid as it is not solely religious or non-religious matters. The political dimension is influential which deconstructs the meaning of charismatic leader in this society. The authority of local kiyai or kiyai kampong is renegotiated by ordinary people when the kiyai is invited to be involved in the political contest by politicians. This article provides an insight on how local Islam has proposed a best example of peaceful conflict resolution in Indonesia. It demonstrates the uniqueness of Indonesian Muslims’ way to solve their internal conflict.